STRATEGI PEMBELAJARAN ANSAMBEL MUSIK SEBAGAI PENGUATAN KARAKTER SISWA BERBASIS AJARAN TAMANSISWA SD KATOLIK SANTA THERESIA KOTA TERNATE - Huik, Sabina; Moh. Rusnoto Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the strategies for learning musical ensembles as character strengthening is the Trihayu approach. The aim of this research is to analyze and develop strategies to strengthen student character that are in line with Tamansiswa teachings, especially with the Trihayu teaching approach. This research used qualitative methods at the Santa Theresia Catholic Elementary School, Ternate City. With resource persons from class teachers and music art teachers, using data analysis techniques for data collection, data reduction, presenting data, and verification/drawing conclusions. The music ensemble teaching strategy as strengthening students' character is in line with Trihayu's approach which is carried out in various ways such as habituation, modeling, using media and providing contextual examples so that it is hoped that students' closeness to nationalism will be well established.